Can you swim? Teaching teachers of swimming and water safety - Blitvich, J.; Petrass, L.; McElroy, G. K. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
University of Ballarat Exercise and Sport Science degree students must complete a swimming and water safety unit in first year. Their entry level skills vary widely from very limited to national-level competitive swimming. This paper, part of the wider `Can you swim` project, describes a swimming and water safety intervention embedded within their course, designed to enable students to enhance their understanding of knowledge, attitudes and behaviours that contribute to drowning risk; develop personal swimming and survival skills; and establish teaching strategies and sequences for enhancing aquatic skills of others.